Mode of delivery, analgesic, and neuromusculoskeletal profile of women developing new onset lower back pain postpartum - Steyn, Joretha (University of the Witwatersrand, Johannesburg, 2024)
The aim of this cohort study, a longitudinal study that follows participants over a period, was to establish the profile of women developing lower back pain (LBP) postpartum by investigating the association between LBP and the mode of delivery, analgesia used and the neuromusculoskeletal structures involved. A baseline assessment was done on 16 participants, four were excluded as per the exclusion criteria, with outcome measures such as the Oswestry LBP disability questionnaire and the visual analogue scale (VAS) at 24 weeks gestation and a follow up assessment at six- and 12-weeks postpartum. Irrespective of the analgesia used during labour (epidural, combined spinal and epidural (CSE), general anaesthesia or no analgesia) or the mode of delivery, be it natural, an elective caesarean section or an emergency caesarean section, 50% (n=6) had pain at six weeks postpartum and 14% (n=7) at 12 weeks postpartum. The VAS and Oswestry LBP disability questionnaire averaging 4/10 and 12.6% respectively. It should be noted that the 14% (n=7) that had pain at 12 weeks had a scheduled caesarean section done under general anaesthesia which leads us to agree with Eisenach, et al., (2013) that labour itself does have a protective physiological mechanism against developing pain postpartum. It is recommended that a future study should extend the time frame of data collection to two to three years to ensure a larger sample size to get a more significant and clearer picture of the development of LBP postpartum and the factors or structures involved. This in turn can ensure a more comprehensive preventative strategy to be researched to decrease the development of LBP postpartum.
A research report for a master’s degree by coursework submitted in partial fulfillment of the requirements for the degree Master of Science in Physiotherapy field of Orthopaedic Manipulative Physiotherapy. to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg 2024
Keywords: Lower back pain; Post-partum; Type of delivery; Type of anesthetic; UCTD; SDG-3: Good health and well-being